Mice lacking Faim2 show increased cell death in the MPTP mouse model of Parkinson disease. Issue 5 (11th October 2016) - Komnig, Daniel; Schulz, Jörg B.; Reich, Arno; Falkenburger, Björn H.
Abstract: The death receptor Fas/CD95 mediates apoptotic cell death in response to external stimuli. In neurons, Fas‐induced apoptosis is prevented by Fas‐apoptotic inhibitory molecule 2 (Faim2). Mice lacking Faim2 showed increased neurodegeneration in animal models of stroke and bacterial meningitis. We therefore tested the relevance of Faim2 in a classical animal model of Parkinson disease and determined the toxicity of 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) in Faim2‐deficient mice. Without MPTP treatment, there was no difference in the dopaminergic system between Faim2‐deficient mice and control mice. MPTP was applied i.p. in doses of 30 mg per kg on five consecutive days. Fourteen days after the last MPTP injection, the number of dopaminergic neurons in the lateral substantia nigra, assayed by stereological counting, was reduced by 39% in control mice and 53% in Faim2‐deficient mice. The density of dopaminergic fibers in the dorsal striatum was reduced by 36% in control mice and 69% in Faim2‐deficient mice, in the ventral striatum 44% in control mice and 76% in Faim2‐deficient mice. Fiber density recovered at 90 days after MPTP with similar density in both groups. Striatal catecholamine levels were reduced by 81–84% in both groups and recovered at 90 days. Faim2 expression was documented in mouse midbrain using quantitative reverse transcription‐PCR (qRT‐PCR) and found decreased after MPTP administration. Taken together, our findings demonstrate increased degeneration of dopaminergic neurons with Faim2 deficiency, indicating that Fas‐induced apoptosis contributes to cell death in the MPTP mouse model. Along with the decreased expression of Faim2 after MPTP, this finding indicates that boosting Faim2 function might represent a therapeutic strategy for Parkinson disease. Abstract : Parkinson disease is characterized by apoptotic death of dopaminergic neurons. We show here that mice lacking the neuronal protein 'Fas Apoptotic Inhibitory Molecule 2' (Faim2) display increased neurodegeneration in a model of Parkinson disease where death of dopaminergic neurons is induced by administration of the neurotoxin 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP). Our findings indicate that Faim2 protects dopaminergic neurons from Fas‐induced apoptosis in the MPTP model. MPTP administration reduces Faim2 expression in wild‐type mice, suggesting that boosting Faim2 might be neuroprotective in Parkinson disease.